Analisis Ekonomi Penggunaan Tepung Kiambang (Salvinia Molesta) Terfermentasi dalam Ransum Ayam Jawa Super - A P Tanjung; T Rumiyani; Nurhayati (Politeknik Negeri Lampung, 2020)
This study aimed to analyze the production cost of using fermented kiambang flour in Super Javanese chicken ration. The research method used descriptive method. Data collection was done by taking samples from controls and treatment with a total of 15 heads each at the end of maintenance. The average yield on the administration of fermented kiambang flour of 10% resulted in an IOFC value of Rp. 13,553 and control resulted in an IOFC value of Rp. 12,868. The average yield on the administration of fermented kiambang flour 10% produces a BEP value of Rp. 31,584 and control produces a BEP value of Rp. 33,636. The average yield on the administration of fermented kiambang flour 10 % produces an R/C value of 1,215 and at the control stage produces an R/C value of 1,180. The average yield on the administration of fermented kiambang flour of 10% produces a B/C value of 0.215 and at the control stage produces a B/C value of 0.180. It can be concluded that the use of fermented kiambang flour as much as 10% on super Javanese chicken rations can reduce production costs and have economic value.